Liberal party performance when rival parties shift position on the left-right axis. Issue 6 (November 2016) - Margulies, Ben
Abstract Building from the work of Nagel and Wlezien (2010) in the United Kingdom, I theorize that liberal parties gain votes from conservative parties across 26 established democracies when conservative parties move to the right, and from social democratic parties when those parties move to the left, as judged by the right-left scale provided by the Comparative Manifesto Project. I also hypothesize that liberal strength at election(t−1) pushes conservative and social democratic parties farther towards the extremes of the left-right spectrum. The models tested herein demonstrate that this in fact does happen cross-nationally, although the effect is considerably weaker than the relationship Nagel and Wlezien identified in the United Kingdom.